Study of properties of sintered chrome-nickel-niobium steel - Holub , I.V.; Nosko , O.A.; Koval , D.O.; Kovzik , A.M.; Kushnir , Yu.O. (Theory and Practice of Metallurgy, 2024)
Goal. Conducting an analysis of modern technologies for the production of powder materials for additive manufacturing technologies, determining their key characteristics and clarifying the impact of production on the final quality of products under given operating conditions. Study of the mechanical properties and corrosion resistance of a sintered chrome-nickel-niobium steel product made by additive technology. Method. Theoretical and experimental studies of samples of sintered powder steels according to ISO 2738, ISO 4003 for powders, as well as for mechanical properties of samples according to ISO 3325:2017; ISO 3928:2014; ISO 6892:2019; ISO 6506-1:2019. The results. The mechanical properties and corrosion resistance of sintered chrome-nickel-niobium steel under the specified operating conditions of the products were studied. The effect of porosity on the heat resistance and mechanical properties of sintered materials during the production of products by the Selective laser melting method was established. Scientific novelty. Obtaining new information regarding the mechanical and heat-resistant characteristics of steels proposed for additive technology at elevated temperature conditions of product operation. Elucidation of the effect of contacts of sintered powder particles on the mechanical properties of the powder product. Practical significance. It has been established that sintered materials containing a greater number of heat-resistant components have lower open porosity and are more corrosion-resistant at elevated temperatures. Proposed technological methods of increasing the corrosion resistance of sintered chromium-nickel-niobium steels. Expansion of the range of powder materials for additive technologies.